2012
DOI: 10.1186/2045-709x-20-26
|View full text |Cite
|
Sign up to set email alerts
|

The effect of spinal manipulative therapy on experimentally induced pain: a systematic literature review

Abstract: BackgroundAlthough there is evidence that spinal manipulative therapy (SMT) can reduce pain, the mechanisms involved are not well established. There is a need to review the scientific literature to establish the evidence-base for the reduction of pain following SMT.ObjectivesTo determine if SMT can reduce experimentally induced pain, and if so, if the effect is i) only at the level of the treated spinal segment, ii) broader but in the same general region as SMT is performed, or iii) systemic.DesignA systematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
88
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(97 citation statements)
references
References 53 publications
(101 reference statements)
5
88
4
Order By: Relevance
“…Furthermore, this review included postgraduate theses which are often not taken into account. Based on these new findings, the current results do not support previous findings in those patients that SM may have the distal analgesic effect (Coronado et al, 2012;Millan et al, 2012), although there is a concern about small number of included studies.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…Furthermore, this review included postgraduate theses which are often not taken into account. Based on these new findings, the current results do not support previous findings in those patients that SM may have the distal analgesic effect (Coronado et al, 2012;Millan et al, 2012), although there is a concern about small number of included studies.…”
Section: Discussioncontrasting
confidence: 80%
“…In the study by Winters et al (1997) pain in the superior part of the trapezoid muscle and scapular region was included, although such pain could be caused by cervical disorders (Dwyer et al, 1990;Grubb and Kelly, 2000). In other recent reviews, Coronado et al (2012) investigated the analgesic effects of SM and Millan et al (2012) examined those of spinal manipulative therapy including both SM and spinal mobilization. Whereas these reviews included only studies investigating the effect of SM or spinal manipulative therapy on experimentally induced pain regardless of whether subjects are symptomatic, the current review only included those examining pain changes in clinical populations.…”
Section: Discussionmentioning
confidence: 99%
“…Manual therapy techniques can play a role in these interactions as they trigger a cascade of neurophysiological events starting from some form of mechanical (manual) stimulation of the body (Bialosky 2008). Evidence for these neurophysiological events comes from clinical research which show increases in pain thresholds (PTs) directly after spinal manual therapy interventions in healthy participants, in participants subjected to experimentally induced pain, and in patients with musculoskeletal pain (Coronado et al 2012, Millan et al, 2012. In the reviews of Millan and colleagues (2012) and Coronado and colleagues (2012), it was concluded that manual therapy techniques carried out at the spinal column have significant pain modulating effects, although the clinical relevance of these effects remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…47 It is hypothesized, but not definitely proven, that these thrusts create a stimulus to spinal tissues that may result in analgesia. 12,20,22,50 A large body of research has generally supported efficacy and effectiveness of SMT for the treatment of LBP, with overall effect-size improvements in pain following SMT that are typically modest when compared to placebo treatment or to no treatment at all. 16,19,33,[36][37][38]42,55,59,62 These findings suggest a heterogeneous response between patients receiving SMT.…”
Section: T T Conclusionmentioning
confidence: 99%